2006
DOI: 10.1002/art.22258
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus pulposus notochord cells secrete connective tissue growth factor and Up‐regulate proteoglycan expression by intervertebral disc chondrocytes

Abstract: Objective. To identify the components of conditioned medium obtained from intervertebral disc nucleus pulposus-derived canine notochord cells, and to evaluate the capacity of such factors to affect discderived chondrocyte gene expression of aggrecan, versican, and hyaluronic acid synthase 2 (HAS-2) as a function of culture conditions.Methods. Canine notochord cells obtained from nonchondrodystrophic dogs were cultured within alginate beads under conditions of serum deficiency (Dulbecco's modified Eagle's mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(151 citation statements)
references
References 47 publications
9
138
1
1
Order By: Relevance
“…proteoglycans, collagens and keratins, and organelle-derived proteins. However, specific growth factors, potentially responsible for NCCM's regenerative effect, were not identified, which is in contrast with previous studies in which CTGF was identified in canine (Erwin et al, 2006) and porcine (Gantenbein et al, 2014) NCCM. This discrepancy may be due to the method of NCCM generation.…”
Section: Nccm Exerts Cross-species Anabolic Effects On Clcscontrasting
confidence: 98%
See 2 more Smart Citations
“…proteoglycans, collagens and keratins, and organelle-derived proteins. However, specific growth factors, potentially responsible for NCCM's regenerative effect, were not identified, which is in contrast with previous studies in which CTGF was identified in canine (Erwin et al, 2006) and porcine (Gantenbein et al, 2014) NCCM. This discrepancy may be due to the method of NCCM generation.…”
Section: Nccm Exerts Cross-species Anabolic Effects On Clcscontrasting
confidence: 98%
“…Up to date, only few studies reported on the potential biologically active NCCM factors. Connective tissue growth factor (CTGF) was found in canine (Erwin et al, 2006) and porcine (Gantenbein et al, 2014) NCCM and alpha-2-macroglobulin, clusterin and tenascin were detected in porcine NCCM (Purmessur et al, 2011).…”
Section: Identification Of the Bioactive Factors In Nccmmentioning
confidence: 99%
See 1 more Smart Citation
“…Future experiments will test the influence of cell-cell contact by seeding pNCs and bNPCs into alginate beads enabling cell-cell interaction and also the importance of hypoxic conditions. Gene expression revealed a significant up-regulation of Col 1 and Col 2 by the pNCs in the presence of bNPCs, which confirms previous findings of Boyd [3] and Aguiar et al [1] that NCs express certain stimulating cytokines, which seems evident and has been demonstrated using conditioning media [3,9,22]. Korecki et al also detected that SOX-9 (transcription factor for chondrogenesis) was down-regulated if human mesenchymal stem cells (hMSCs) are exposed to notochordal conditioned medium (NCM) as compared to a chondrogenic medium containing TGF-b.…”
Section: Optimal Cell Ratiosupporting
confidence: 88%
“…Ainsi, l'hypothèse d'une différenciation progressive des cellules notochordales en nucléopul-pocytes fait actuellement l'objet d'investigations. De plus, de récentes études ont démontré que les cellules notochordales stimulent la synthèse de protéoglycanes (PG) par les nucléopul-pocytes ainsi que leur prolifération, grâce à la sécrétion notamment du connective tissue growth factor (CTGF/CCN2) (Figure 2) [11]. Ces protéoglycanes retiennent les molécules d'eau et offrent au NP des propriétés de déformabilité et de résistance aux contraintes méca-niques incomparables et indispensables au maintien de la dynamique rachidienne [2].…”
Section: Disque Intervertébral Sain Disque Intervertébral Dégénéréunclassified